RDC-1000 Chemical NanoDisc: A new molecular approach for low-cost data storage using colorimetric coding - Barack Ndenga (My University, 2025)
Modern digital storage systems are predominantly based on silicon microelectronics, which—despite their ubiquity—face increasing challenges related to durability, cost, energy demands, and environmental impact. These limitations are especially critical in developing regions where infrastructure and access to advanced hardware remain restricted. To address this gap, this paper introduces a novel chemical-based data storage approach: NanoDisqueChimique RDC-1000, a prototype system designed to encode and store binary data using molecular colorimetric signals. The core principle involves mapping digital bits to chemically distinct states using visually detectable pigments. These states are read via a low-cost optical sensor (TCS3200) interfaced with an Arduino Nano microcontroller, enabling translation of chemical information into digital signals. This fusion of chemistry and microelectronics creates a tangible, physical representation of digital data—transforming molecules into memory units. The system is designed to be inexpensive, scalable, energy-independent, and highly adaptable for African scientific and educational contexts. It provides a blueprint for data archiving where electronic resources are scarce or unstable, offering not only technological innovation but also a decolonized pathway to local hardware innovation. Preliminary experimental results confirm the successful encoding, physical storage, and digital reconstruction of various file types, including text, simple images, and audio/video data converted into binary form. The system shows reliable performance with strong color stability over several weeks and decoding accuracy above 99%. This proof-of-concept opens a new frontier for hybrid molecular-electronic storage systems, bridging chemistry, computing, and accessible innovation. The NanoDisqueChimique RDC-1000 lays the groundwork for future research into long-term, low-cost, and decentralized memory architectures—particularly suited for the Global South.
This research article presents the RDC-1000 NanoChemicalDisk, an innovative molecular data storage prototype designed for low-resource Nano. This hybrid chemical-electronic platform enables the physical storage and digital reconstruction of files such as text, images and binary streams (e.g., audio/videoenvironments.This system encodes binary information using pH-sensitive pigments and gold nanoparticles, with the data read via a TCS3200 color sensor connected to an Ardui microcontroller.The project proposes a revolutionary solution for decentralized and energy-autonomous data archiving, particularly relevant for African scientific contexts.With a decoding accuracy of more than 99% and chemical stability of more than six weeks, this method opens new horizons for the development of sustainable memory architectures,silicon-free.This is the fourth scientific publication by Ndenga Lumbu Barack (aka BarackEinstein97), completed at the age of 23, as part of a series growing number of Africa-centric disruptive innovations in physical chemistry, data science and speculative computing.